Governamentalidades neoliberais e dispositivos de segurança - LEMOS, Flávia Cristina Silveira (2016)
This article aims at a theoretical debate through the analysis of Michel Foucault and Robert Castel, among others, about the security mechanisms and strategies of neoliberal governmentality in contemporary society. Foucault's courses In defense of society, Security, territory and population and The Birth of Biopolitics have opened a relevant discussion about the racism of state and society, its paradoxes in democracies, and effects on the emergence of North America and Germany's neoliberalism after World War II, which was broadcast to other countries, especially in the nineties of the twentieth century, with each country's specificities, but with connection points that allow us to draw a diagram of how society security operates for the conduct of government tactics, also called governmentality by Foucault.